LITERATUR REVIEW : TERAPI SPIRITUAL TERHADAP KUALITAS HIDUP PASIEN CHRONIC KIDNEY DISEASE (CKD) - Aprilianti, Fanizha Laila; Listyarini, Anita Dyah; Charista, Anindya; Safira, Anita Dila; Muniroh, Fitri Ambarwati; Muntiari, Lini (Asosiasi Dosen Muda Indonesia, 2024)
Background : CKD is a late-stage kidney disease that can be caused by various things in which the body's ability fails to maintain metabolism and electrolyte fluid balance, which causes complications of hypertension and diabetes mellitus (Jainurrahma et al, 2021). The prevalence of chronic kidney failure in Indonesia has increased in 2018 to 0.38% or as many as 713,783 people based on a doctor's diagnosis in residents aged 15 years and over. Purpose: to find out the application of spiritual healing to the quality of life of Chronic Kidney Disease (CKD) patients. Method : research used by analyzing articles and searching through Google Scholar using the keywords